2017
DOI: 10.1097/paf.0000000000000346
|View full text |Cite
|
Sign up to set email alerts
|

Coprophagic Asphyxiation in an Intellectually Disabled Woman

Abstract: The ingestion of one's own feces is referred to as coprophagia. In this report, the author discusses a case of coprophagia-associated death in a 36-year-old woman. The woman had a history of intellectual disability, bipolar disorder, and schizoaffective disorder and was living in a group home. At autopsy, examination of the upper airway revealed 4 distinct spherical boli of impacted fecal matter in the oral cavity and pharynx. Death was attributed to asphyxia due to aspiration of stool bolus during an episode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…It has been suggested that the link between attention-deficit hyperactivity disorder (ADHD) and pica could be due to poor impulse control or dysfunctions in the dopaminergic system (Herguner 2010). • Dental pain (Ayanouglou 2011) • Increased appetite due to medication (Erickson 2017) • Dialysis (Katsoufis 2012) • Sickle cell anaemia (El-Mekkawy 2014)…”
Section: Mental Disordersmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that the link between attention-deficit hyperactivity disorder (ADHD) and pica could be due to poor impulse control or dysfunctions in the dopaminergic system (Herguner 2010). • Dental pain (Ayanouglou 2011) • Increased appetite due to medication (Erickson 2017) • Dialysis (Katsoufis 2012) • Sickle cell anaemia (El-Mekkawy 2014)…”
Section: Mental Disordersmentioning
confidence: 99%
“…The role of nutritional deficiencies in pica and whether they are cause or consequence is therefore unclear.
Physical and neurobiological conditions associated with pica Physical Conditions leading to malabsorption, poor nutritional status or anaemia, including gastric bypass surgery and coeliac disease (Gupta 2007) Micronutrient deficiencies (iron/zinc/calcium) (Erickson 2017) Malnutrition (Lerner 2008) Dental pain (Ayanouglou 2011) Increased appetite due to medication (Erickson 2017) Dialysis (Katsoufis 2012) Sickle cell anaemia (El-Mekkawy 2014) Neurobiological Diminished dopaminergic transmission (Barrett 2008) Elevated serotonin levels (Barrett 2008) Decreased/increased endogenous opiate (Barrett 2008)
…”
Section: Associations With Picamentioning
confidence: 99%
See 3 more Smart Citations